2007
DOI: 10.2967/jnumed.106.037440
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Estrogen, Progesterone, and C-erbB-2 Receptor States on 18F-FDG Uptake of Primary Breast Cancer Lesions

Abstract: The purpose of this prospective study was to investigate whether correlations exist between 18 F-FDG uptake of primary breast cancer lesions and predictive and prognostic factors such as estrogen receptor (ER), progesterone receptor (PR), and C-erbB-2 receptor (C-erbB-2R) states. Methods: Before undergoing partial or total mastectomy, 213 patients with newly diagnosed breast cancer underwent 18 F-FDG PET (5.2 MBq/kg of body weight). The maximum standardized uptake value (SUV) of the primary lesion was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 29 publications
5
42
6
Order By: Relevance
“…This tendency has also been reported previously [11][12][13][14][15][16]. Kawamura et al demonstrated that FDG uptake was affected by the number of metabolically active tumor cells [17].…”
Section: Discussionsupporting
confidence: 66%
“…This tendency has also been reported previously [11][12][13][14][15][16]. Kawamura et al demonstrated that FDG uptake was affected by the number of metabolically active tumor cells [17].…”
Section: Discussionsupporting
confidence: 66%
“…Clinical studies have also found a positive correlation between Ki67 staining and uptake of 18 F-FDG in BC (31)(32)(33)(34), although this relationship is not well defined for lobular carcinoma, which has lower uptake of 18 F-FDG than does ductal carcinoma (31)(32)(33)35). Clinically, most data suggest there is no relationship between HER2 expression evaluated by immunohistochemical staining and tumor uptake of 18 F-FDG (32)(33)(34)36). Only Ueda et al found a positive correlation between expression of HER2 and tumor uptake of 18 F-FDG (35).…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting results have been reported as the correlation between FDG uptake and PR status. Some studies have claimed higher SUVmax in the PR (−) breast cancer [39,40], but other reports showed no association between PR status and FDG uptake [41,42]. Ekmekcioglu et al [42] suggested that the cut-off level of the PR limit of positivity might be relevant to the result.…”
Section: Discussionmentioning
confidence: 99%